PKI as a way to leverage DRM interoperability - Serrão, C.; Dias, J.; Delgado, J. (Proc Proceedings of the IADIS International Conference on Telecommunications, Networks and Systems 2007 (TNS2007), 2007)
Managing fair content access to digital objects in a digital World is a hard task. This task involves, among other things, the capability to manage a large number of users/actors, devices and software components allied to the capacity to establish trust relationships and trust environments between them. To establish this trust environment, digital object rights management solutions often implement their own specific security services that are, most of the times, not compatible between them. These implemented solutions are sometimes incomplete and may lead to potential security issues (a false sense of security). This article focuses on the fact that PKI services can be used to provide the necessary security services and the appropriate key management services to fulfill the DRM requirements in the establishment of needed trust environments.